Letter - Stockton and Thornaby Trades & Labour Council, 9 May 1926 (page 1) (Stockton)
1926-05-09 "Letter - Stockton and Thornaby Trades & Labour Council, 9 May 1926 (page 1)" [g0133001.jpg], 9 May 1926, Stockton and Thornaby Trades & Labour Council Local Organisation